2010 International Conference on Indoor Positioning and Indoor Navigation 2010
DOI: 10.1109/ipin.2010.5646888
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and evaluation of acceleration based step length estimators for handheld devices

Abstract: A comparison between different step length estimation algorithms for pedestrian dead reckoning is presented. This work covers theoretic evaluation of the estimators' performance and presents a comparison based on measurement data. Measurement data were taken from a group of five adults walking at three different velocities. For reference, the sensors were placed according to the recommendation given for each algorithm. In respect to everyday usability the performance of the estimators is furthermore evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 5 publications
0
57
0
Order By: Relevance
“…[20,21]. Here the acceleration on the PCOM (Pedestrian's Centre Of Mass) is measured, which is the point at the back near the fourth lumbar vertebra [22]. The estimated step length is calculated as…”
Section: Pdrmentioning
confidence: 99%
“…[20,21]. Here the acceleration on the PCOM (Pedestrian's Centre Of Mass) is measured, which is the point at the back near the fourth lumbar vertebra [22]. The estimated step length is calculated as…”
Section: Pdrmentioning
confidence: 99%
“…There are several step length estimation methods that have been proposed for different applications in the past [21][22][23]. A comparison of several popular methods has revealed that the one proposed by Weinberg et al is best suited for a waist-mounted IMU [16,26].…”
Section: Knowledge-based Sle Algorithm Based On Fuzzy Logicmentioning
confidence: 99%
“…The rationale is that of using a dead reckoning-like approach [8,9]: detect the human steps by means of a proper analysis of the accelerometer measurements [33], then use the combination of magnetometer and accelerometer measurements to estimate the movement direction with respect to the north [28].…”
Section: System Description and Relation To Previous Workmentioning
confidence: 99%
“…An estimation of the initial position (u 0 , v 0 ) is assumed to be (a priori) available. The step length s t is assumed to be provided by a proper analysis of the accelerator measurements [33]. Alternatively, s t can be fixed to a constant value (an approximation of the mean step length): the tracking algorithm described in Section 3 is designed to compensate (relatively small) step length errors.…”
Section: System Description and Relation To Previous Workmentioning
confidence: 99%